2014
DOI: 10.1051/0004-6361/201424424
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the radio-loud phase of broad absorption line quasars

Abstract: Context. Broad absorption lines (BALs) are present in the spectra of ∼20% of quasars (QSOs); this indicates fast outflows (up to 0.2c) that intercept the observer's line of sight. These QSOs can be distinguished again into radio-loud (RL) BAL QSOs and radio-quiet (RQ) BAL QSOs. The first are very rare, even four times less common than RQ BAL QSOs. The reason for this is still unclear and leaves open questions about the nature of the BAL-producing outflows and their connection with the radio jet. Aims. We explo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The key result of this work is the lack of strong differences in the UV spectral properties of RL and RQ BAL quasars, as well as between their fundamental physical properties, confirming the findings from the rest-frame optical of Bruni et al (2014). Though Table 2 shows that there are some differences, many of them are interrelated.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The key result of this work is the lack of strong differences in the UV spectral properties of RL and RQ BAL quasars, as well as between their fundamental physical properties, confirming the findings from the rest-frame optical of Bruni et al (2014). Though Table 2 shows that there are some differences, many of them are interrelated.…”
Section: Discussionsupporting
confidence: 78%
“…Runnoe et al (2013) found that RL BAL quasars are very similar to RQ BAL quasars in their optical emission-line properties, and RL BAL quasars are more "BAL-like" than "RL-like" in their EV1 properties. Bruni et al (2014) find that the rest-frame optical properties of RL and RQ BAL quasars, and physical parameters derived from them, are identical. Here, we examine the rest-frame ultraviolet (UV) spectral properties of a well-matched sample of 73 RL and 473 RQ BAL quasars, and search for significant differences in their properties.…”
Section: Introductionmentioning
confidence: 74%
“…The radio loudness associated to their powerful radio jets is probably driven by the efficient extraction of rotational energy from both the disk (Blandford & Payne 1982) and the black hole (Blandford & Znajek 1977); however, the exact physical mechanism behind the launching and acceleration of the most powerful radio jets is still under investigation (see Czerny & You 2016, for a recent review). We note how there are no apparent differences in observed properties such as black hole mass, Eddington ratio, and BLR size between radio-loud and radio-quiet BAL QSOs (Bruni et al 2014), suggesting that the physical difference between them might reside in different black hole spin values. The scarcity of powerful radio-loud FR II BAL QSOs is probably due to the combination of a large black hole mass needed to have a RL AGN (Laor 2000), which is possibly related to the merger history of the host galaxies, where coherent mergers can increase the value of the BH spin (e.g., Fanidakis et al 2011), and a high or very high ṁ to have a radiation driven BAL wind, all in all giving a small region of the M BH − ṁ parameter space where the phenomenon of radio-loud BAL QSO can manifest.…”
Section: Discussionmentioning
confidence: 77%
“…Any association with the X-ray weakness appears rather challenging in the standard paradigm. J1425+54: A claim for a C iv BAL with absorption index AI 269 km s −1 was made by Bruni et al (2014). The feature seems to be actually resolved in three narrow components, and its origin remains somewhat uncertain.…”
Section: Appendix A: Gallery Of X-ray Spectramentioning
confidence: 99%